Predictors of re-attendance at biennial screening mammography following a false positive referral: A study among women in the south of the Netherlands - Adri C. Voogd; Zsófi Molnar; Joost Nederend; Robert-Jan Schipper; Luc J.A. Strobbe; Lucien E.M. Duijm (Breast, 2024)
Aim: A false positive (FP) referral after screening mammography may influence a woman's likelihood to re-attend the screening program. The impact of having a FP result in the first or subsequent screening round on re-attendance after a FP result was investigated. In addition, we aimed to study differences in re-attendance rates between women who underwent non-invasive and invasive additional examinations as part of the diagnostic work-up following a FP referral. Methods: A consecutive series of 13,597 women with a FP referral following biennial screening mammography in the south of the Netherlands between 2009 and 2019 was included. Results: The screening re-attendance rate was 81.2% after a FP referral, and 91.3% when also including women who had clinical mammographic follow-up. Women who received a FP referral in the first screening round were less likely to re-attend the screening programme in the following three years, compared to those with a FP test in any subsequent round (odds ratio (OR): 0.59, 95%-confidence interval (CI): 0.51–0.69). Women with a FP referral who underwent invasive examinations after referral were less likely to re-attend the screening programme than those who only received additional imaging (OR, 0.48; 95% CI 0.36–0.64). Conclusion: Women with a FP referral are less likely to re-attend the screening programme if this referral occurs at their first screening round or when they undergo invasive diagnostic workup. Hospitals and screening organizations should prioritize informing women about the importance of re-attending the programme following a FP referral.